Secure ICT services for mobile and wireless communications. (5th June 2007) - Siddiqi, J.; Orth, W.; Meyer, N.; Tuisku, M.; Pipan, G.; Gallego, M.; Garcia, J.A.; Cecchi, M.
The paper reports on the current research activities related to the delivery of a Federated Global Identity Management framework for provisioning secure Information Communication Technologies (ICT) services; this represents a significant step towards the development of global federated security services for the Web, Grid and particularly for future Mobile and Wireless communication (ICT platforms). The overall aim of this research is to provide seamless traversal to access distributed resources in the heterogeneous Web, Grid, and particularly Mobile and Wireless spaces. Furthermore, in order to consider the value and usefulness of the Trust-ME framework, its strategic impact is assessed in terms of its proposed application to a real world integrated scenarios in three distinct domains of telecommunications, surveillance and virtual gaming.